Návrh a implementace řešení Business Intelligence v malém podniku - Viskievič, Gergő (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práca sa zaoberá návrhom a implementáciou Business Intelligence riešenia so zameraním do oblasti návrhu a implementácie dátového skladu a reportingu v malom podniku, podnikajúci v oblasti digitálnych služieb. Predstavuje oblasť Business Intelligence, spôsoby implementácie a technologické riešenia. Na základe analýzy informačných potrieb podniku a používaných systémov je navrhnutá a implementovaná kompletná architektúra Business Intelligence.

The diploma thesis focuses on the design and implementation of a Business Intelligence solution with a dedication to the design and implementation of a data warehouse and reporting in a small business, operating in the field of digital services. It introduces the field of Business Intelligence, implementation methods and technology solutions. Based on the analysis of information needs of the business and used systems, a complete Business Intelligence architecture is designed and implemented.
Design and Implementation of Business Intelligence Solutions in a Small Business
Keywords: Business Intelligence; dátový sklad; ETL proces; budovanie dátového skladu; reporting; implementácia; riešenie; malý podnik; Business Intelligence; data warehouse; ETL process; data warehouse building; reporting; implementation; solution; small business